Molecular medicine in anesthesia - Albite, Romina D.; Bonofiglio, Francisco C.; García Fornari, Gustavo (Revista del Hospital Italiano de Buenos Aires, 2016)
The anesthesia’s future suggests to imply molecular biology among its disciplines in order to improve creating personalized therapies. The genes’ analysis allows choosing about drug administration, researching pain medicine, testing techniques and development of new anesthetic agents in order to ensure the efficiency of treatments or procedures